ChemInform Abstract: Synthesis of exo‐Enamides from Protected Lactams Using a Modified Julia Olefination Reaction: Application to the Synthesis of Spiroaminal Fragments. Issue 12 (March 2015) - Gigant, Nicolas; Habib, Samuel; Medoc, Marie; Goekjian, Peter G.; Gueyrard, David; Gillaizeau, Isabelle
Abstract Lactams (I), (IX), and (XIV) are tested as substrates in the title process.